Designing Vocational Training Policies For The Next Ten Years In An Outermost European Region: Highlights From A Participatory Process - Bettencourt, L.; Simões, F.; Fernandes, B. (1st International Conference Rural Youth and the New Youth Guarantee, 2022)
This paper presents a systematic framework of the most needed Vocational Education and Training (VET) reforms in The Azores, a Portuguese outermost region. Our report is based on a participatory research approach involving the perspectives of five different groups of stakeholders. Our data was collected in 18 virtual world-café sessions (n = 164 participants – 58 trainees; 21 trainers; 42 institutional representatives; 21 unemployed people registered at local public employment agencies; and 22 businesspersons; M age = 45.20; 60.37 women). Based on content analysis, we identified three main priorities to restructure vocational training policies: (a) VET perception and valorization, comprising strategies to disseminate a more positive social representation of VET in the region; (b) horizontal coordination between stakeholders, including effective ways of coordinating and sharing information; and (c) vertical coordination in terms of VET improvements of curricula, funding models, and investments in the sector’s human capital. Our correspondence analysis did not show significant differences regarding the prevalence of the three priorities across the five groups of stakeholders. We interpret and contextualize our results according to relevant publicly available data about the region, and an integrated governance lens to inform policy design in outermost territories.